The intratumoral landscape of T cell receptor repertoire in esophageal squamous cell carcinoma - Meng Yang; Dan He; Yu Sun; Yunquan Guo; Yu Ma; Lin Feng; Meng Liu (Journal of Translational Medicine)
Abstract Background Esophageal squamous cell carcinoma (ESCC) is a malignant neoplasm with detrimental implications for human health. The landscape of ESCC therapy has been revolutionized by the introduction of immunotherapy, specifically involving immune checkpoint inhibitors (ICIs). A number of studies have documented the prognostic significance of T-cell receptor (TCR) repertoire and its association with many tumors. Nevertheless, the TCR repertoire landscape and its significance in ESCC still need to be explored. Methods In this study, we conducted RNA-Seq analysis to investigate the characteristics of the TCR repertoire in 90 patients. Moreover, high-throughput TCR sequencing was performed on tumor tissues from 41 patients who received immunotherapy. Additionally, a comprehensive analysis of the T-cell receptor repertoire landscape within ESCC tumors was carried out through immunohistochemical staining on all patient samples. Results We noticed a diminished diversity of TCR repertoire within the tumor compared to its adjacent normal tissue. In terms of immunotherapy responses, non-responsive patients exhibited higher TCR repertoire diversity indices and an increased frequency of common V and J genes. Additionally, elevated TCR repertoire diversity correlated with improved overall survival rates. Lastly, immunohistochemical staining results indicated a correlation between TCR repertoire diversity and the tumor immune microenvironment (TIME). Conclusions Our study primarily describes the landscape of TCR repertoires in ESCC through three aspects: differences in tumor tissues, immune response to immunotherapy, and survival prognosis of patients. These results emphasize the importance of TCR repertoire characteristics as unique and relevant biomarkers for ESCC immunotherapy.